Long business cycles theory as an instrument of economic growth determination - Kvitka, Anton Vladimirovich (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The economy of any country, including Ukraine, is affected by the constant oscillations, which in the scientific com-munity are called “business cycles”. In his studies, a well-known Ukrainian economist Mikhail Tugan-Baranowski had shown an interest towards this topic, and later – so had his student Nikolai Kondratiev, who developed the theory of long cycles (40-60 years). This theory makes it possible to trace the dynamics of long-term economic development, which, in its turn, is necessary for the further prognostication and searching the way out of the crisis situations, inter alia – the current crisis in Ukraine.